Implementasi Model Pembelajaran Make a Match Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Inpres Jongaya Kecamatan Tamalate Kota Makassar - Rahmawati ulath; Rosleni Babo; Syamsuriyanti (Journal of Cultural Relativism (JCR), 2024)
The main problem in this research is the low social studies learning outcomes of fourth grade students at SD Inpres Jongaya, Tamalate District, Makassar City, which is caused by students' lack of creativity in the learning process because they are less involved in teaching and learning activities, the learning process is carried out monotonously. The aim of this research is to improve the social studies learning outcomes of fourth grade students at SD Inpres Jongaya, Tamalate District, Makassar City through the application of the Make a Machine learning model. The research carried out was classroom action research (PTK). This research was conducted in two cycles which included four meetings. The subjects of this research were 21 students in class IV of SD Inpres Jongaya, Tamalate District, Makassar City, consisting of 6 boys and 15 girls. Data collection techniques are observation, tests (evaluation), and documentation. The data obtained is then analyzed using quantitative and qualitative descriptive analysis. The results of the research show an increase in social studies learning outcomes for class IV students at SD Inpres Jongaya, Tamalate District, Makassar City. Likewise, the data from observations in each cycle shows a change in students' attitudes in a positive direction. The above can be seen from the increase in student learning outcomes, namely the class average score in the pre-cycle was 58, then in cycle 1 it was 72 and in cycle II it was 78. The number of students able to achieve a KKM of 75 in the pre-cycle was 6 students, in cycle 1 there were 9 students, and in cycle II there were 21 students. The percentage of completion in the pre-cycle was 28%, cycle 1 42%, and cycle II 100%, so that in cycle II the criteria for 80% of students had reached KKM 75. From the results of the analysis it was concluded that the social studies learning outcomes of class IV students at SD Inpres Jongaya District Makassar City Tamalate can be improved through the Make a Match model.